A Missing Link on Entrepreneurship Education Curricula - Kriswanto Widiawan (International Journal of Industrial Research and Applied Engineering, 2017)
Indeed, there are many failure cases in entrepreneurs’ life. The psychological effects of business failure may produce shame and dysfunctional behavior responses. Do the entrepreneurs consider about the potential of shame they face? Do entrepreneurship education institutions pay attention to business closing as well as its impact to entrepreneurs’ identity?  This research explored the curricula of 66 top business schools which have entrepreneurship specialization. There was a course category, namely self-development, which is important for entrepreneurs to build their mental, self-leadership, self-awareness, self-image, etc. Unfortunately, from 2908 courses offered, only 12.76% courses were related to entrepreneurship and 0.79% courses to self-development issues. The curricula were dominated by business knowledge and business skills. There was a missing link, i.e., “when the business goes wrong”, how to cope with failure, how to overcome shame, guilt, depression, stress, etc. In conclusion, there were lacks of self-development courses in the entrepreneurship education programs. This paper recommends to prepare the students to anticipate and overcome the shame by adding more psychological-related courses in the curriculum.